Smart cities for sustainability : approaches and solutions - Abdelli, Mohammed El Amine; Sghaier, Asma; Akbaba, Atilla; Gamoura, Saia Chehbi; Mohammadian, Hamid Doost (Emerald Publishing Limited, 2023)
The application of technology, in smart cities, to create meaningful sustainability is set to change all our lives. The smart city of the future will be equipped with communication infrastructures to improve the comfort of all citizens, while respecting the environment, and supporting good governance. Information and Communications Technology (ICT) will play a key role, making it possible to better manage infrastructure and transport. Contributors from around the world here present modern insights for use by decision-makers to solve real-world challenges. The authors shed light on forthcoming developments and set out how to plan for increasingly rapid changes. Smart Cities for Sustainability: Approaches and Solutions provides a modern insight for researchers, students, professionals, and decision-makers on the application of digitalization in global cities to achieve their SDG goals.
Includes index.
Keywords: Sustainable urban development.; Business & Economics -- Development -- Sustainable Development.; Sustainability.; elektronické knihy; electronic books